Boreal feather mosses secrete chemical signals to gain nitrogen. Issue 1 (25th June 2013) - Bay, Guillaume; Nahar, Nurun; Oubre, Matthieu; Whitehouse, Martin J.; Wardle, David A.; Zackrisson, Olle; Nilsson, Marie‐Charlotte; Rasmussen, Ulla
Summary The mechanistic basis of feather moss–cyanobacteria associations, a main driver of nitrogen (N) input into boreal forests, remains unknown. Here, we studied colonization by Nostoc sp. on two feather mosses that form these associations (Pleurozium schreberi and Hylocomium splendens) and two acrocarpous mosses that do not (Dicranum polysetum and Polytrichum commune). We also determined how N availability and moss reproductive stage affects colonization, and measured N transfer from cyanobacteria to mosses. The ability of mosses to induce differentiation of cyanobacterial hormogonia, and of hormogonia to then colonize mosses and re‐establish a functional symbiosis was determined through microcosm experiments, microscopy and acetylene reduction assays. Nitrogen transfer between cyanobacteria and Pleurozium schreberi was monitored by secondary ion mass spectrometry (SIMS). All mosses induced hormogonia differentiation but only feather mosses were subsequently colonized. Colonization on Pleurozium schreberi was enhanced during the moss reproductive phase but impaired by elevated N. Transfer of N from cyanobacteria to their host moss was observed. Our results reveal that feather mosses likely secrete species‐specific chemo‐attractants when N‐limited, which guide cyanobacteria towards them and from which they gain N. We conclude that this signalling is regulated by N demands of mosses, and serves as a control of N input into boreal forests.